2007
DOI: 10.1177/10253823070140021801
|View full text |Cite
|
Sign up to set email alerts
|

Empowered women from rural areas of Bolivia promote community development

Abstract: The United States Agency for Development in Bolivia (USAID/Bolivia) created in 2002 PROSALUD- Partners for Development Project (PfD) with the aim of improving the population's well-being. The project used three components: small grant scheme, technical assistance and database system management. Through the small grants scheme, the PfD supported a Community Participation Strategy (CPS) project over a three year period. The project involved the rural areas of six Bolivian departments and suburban areas of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Facilitated structured planning and action oriented women's group sessions moving from problem analysis, strategies, implementation and review in Bolivia, coincided with a decrease in perinatal mortality from 117 to 43 deaths per 1000 live births (p<0.001) and increased participation in women's organisations from 7 to 54% (p<0.001) [45]. In other sites of Bolivia this model led to 73% of participants expressing willingness to use reproductive health services [46], CPR increased from an estimated zero to 27%, clean delivery kits were newly introduced and used in 27% of homebirths, and early breastfeeding increased from 25 to 57% within 3 years [32]. In two projects, inclusion of health, education and agricultural representatives and motivation of community leaders in planning activities led to perceived improvements in community-wide improved health behaviours and increases in health service utilisation in Papua New Guinea [47], [48] although this was not quantified or validated.…”
Section: Resultsmentioning
confidence: 99%
“…Facilitated structured planning and action oriented women's group sessions moving from problem analysis, strategies, implementation and review in Bolivia, coincided with a decrease in perinatal mortality from 117 to 43 deaths per 1000 live births (p<0.001) and increased participation in women's organisations from 7 to 54% (p<0.001) [45]. In other sites of Bolivia this model led to 73% of participants expressing willingness to use reproductive health services [46], CPR increased from an estimated zero to 27%, clean delivery kits were newly introduced and used in 27% of homebirths, and early breastfeeding increased from 25 to 57% within 3 years [32]. In two projects, inclusion of health, education and agricultural representatives and motivation of community leaders in planning activities led to perceived improvements in community-wide improved health behaviours and increases in health service utilisation in Papua New Guinea [47], [48] although this was not quantified or validated.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed females and lower-educated people were more likely to attended community meetings in the project site (Tables 3 and 4 ). It seems common that females are usually more motivated and empowered through a community development program [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skill enhancement can be done using the Participatory Learning and Action (PLA) approach, which is a participatory based method. With this PLA method, skill improvement is done by providing education and practice, as has been done by [16][17][18]. The PLA method which prioritizes community participation in the empowerment process can encourage women in decision making and capacity building [18].…”
Section: Introduction Agriculture In Sukarasa Village Arjasari Sumentioning
confidence: 99%
“…With this PLA method, skill improvement is done by providing education and practice, as has been done by [16][17][18]. The PLA method which prioritizes community participation in the empowerment process can encourage women in decision making and capacity building [18]. This research adopts PLA method to improve the skill of housewives and teenagers at Sukarasa Village.…”
Section: Introduction Agriculture In Sukarasa Village Arjasari Sumentioning
confidence: 99%